Pro-Kontra Poligini Dalam Islam: Upaya Menemukan Titik Tengah - Ansor M. Rusydi (Justicia Islamica, 2005)
This study aims to analyze the debate on polygyny in Islam and to find a middle ground in its understanding. The method used is qualitative with a descriptive-analytical approach, through a literature review of classical and contemporary Islamic legal sources. The results show that polygyny in Islam has a sharia basis, but with strict conditions of justice. The pro opinion emphasizes the legitimacy of polygamy as part of Islamic teachings, while the counter party sees it as a practice that can harm women. In the modern context, reinterpretation is carried out to adapt this practice to the principles of justice and family welfare. This study confirms that a middle ground can be found by understanding polygamy as a conditional option and not as the main norm in marriage, so that it remains in accordance with the maqashid sharia which emphasizes justice and benefit.